2019
DOI: 10.1039/c9ay01804b
|View full text |Cite
|
Sign up to set email alerts
|

A metal ion-regulated colorimetric sensor array: discriminating Chinese Baijiu from other beverages

Abstract: We provide a Baijiu colorimetric sensor array based on metal ions regulated Au NPs aggregation, which can do a correct classification of 16 Baijius with different flavor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 33 Li et al reported that Fe 3+ cations can be used to oxidize the colloidal substances in Baijiu and reduce the entropy of the Baijiu colloidal system. 34 In this case of electrochemical oxidization treatment, the Baijiu colloidal system is directly treated with high oxidization potential. With the aid of high oxidization potential, the electron transfer and polarity change occurs and reduces the entropy value of the Baijiu colloidal system, 34 maintaining the stability of the Baijiu colloidal system.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 Li et al reported that Fe 3+ cations can be used to oxidize the colloidal substances in Baijiu and reduce the entropy of the Baijiu colloidal system. 34 In this case of electrochemical oxidization treatment, the Baijiu colloidal system is directly treated with high oxidization potential. With the aid of high oxidization potential, the electron transfer and polarity change occurs and reduces the entropy value of the Baijiu colloidal system, 34 maintaining the stability of the Baijiu colloidal system.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The redox properties change significantly, which are closely related to colloid structure, colloid size, and cluster compound environment . Li et al reported that Fe 3+ cations can be used to oxidize the colloidal substances in Baijiu and reduce the entropy of the Baijiu colloidal system . In this case of electrochemical oxidization treatment, the Baijiu colloidal system is directly treated with high oxidization potential.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 However, identifying multiple similar analytes is an exigent problem at present. Array-based sensors using cross-reactive sensing units (known as a ''chemical nose'') have been designed as libraries of sensing receptors that differentially react to miniscule differences in analytes, [6][7][8][9] while multi-color colorimetric sensors are considered to distinguish different target concentrations due to their variable color change. 10,11 The responses from these libraries construct a distinctive ''fingerprint'' for every target, and thus a range of analogues can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the etching effect, Ag@AuNPs and TriAgNPs have been employed for the identification of different oxidizing anions and antioxidants, respectively 22,23 . In recent years, it has been reported to distinguish different types of baijiu based on AuNPs aggregation effect, AuNRs silver deposition, and the AgNPRs etching effect [24][25][26] . The colorimetric sensing strategy based on the aggregation mechanism is simpler, more stable, and easier to use than that based on the other two mechanisms.…”
mentioning
confidence: 99%